Litter Decomposition Rate of Avicennia marina and Rhizophora apiculata in Pulau Dua Nature Reserve, Banten - Siska, Febriana; Sulistijorini, Sulistijorini; Kusmana, Cecep (Journal of Tropical Life Science, 2016)
Litter decomposition rate is useful method to determine forest fertility level. The aims of this study were to measure decomposition rate, and analyze the nutrient content released organic carbon, nitrogen, and phosphor from Avicennia marina and Rhizophora apiculata litters during the decomposition process. The research was conducted in the Pulau Dua Nature Reserve, Serang-Banten on A. marina and R. apiculata forest communities. Litter decomposition rate measurements performed in the field. Litter that has been obtained with the trap system is inserted into litter bag and than tied to the roots or trees to avoid drifting sea water. Litter decomposition rate was measured every 15 days and is accompanied by analysis of the content of organic C , total N and P. Our research results showed decomposition rate of A. marina (k= 0.83) was higher than that of R. apiculata (k= 0.41). Differences ofÂ leaf anatomical structure and sea water salinityÂ influenced to the rate of litter decomposition. Organic C released was declined with longer of litter decomposition, on the contrary of releasing N and P nutrients.